A proposed learning environment framework for virtual care - Liu, John; Buckley, Heather; Ho, Kendall; Hubinette , Maria; Abdalkhani, Arman; Holmes , Cheryl; Nathoo, Nawaaz (Canadian Medical Education Journal, 2021)
The way in which health care is delivered has rapidly changed since the onset of the COVID-19 pandemic, with a rapid increase in virtual delivery of clinical care. As a result, the learning environment (LE) in health professions education, which has traditionally been situated in the bricks-and-mortar clinical context, now also requires attention to the virtual space. As a frequently examined topic in the health professions literature, the LE is a critical component in the development and training of future healthcare professionals. Based on a published conceptual framework for the LE from Gruppen et al. in 2019, a conceptual framework for how the LE can manifest through virtual care space is presented here. The four components of personal, social, organizational, physical/virtual spaces are explored, with a discussion of how they can be integrated into virtual care. The authors provide suggestions that health professions educators can consider when adapting their LE to the virtual environment and highlight aspects of its integration that require further research and investigation.